2010
DOI: 10.1073/pnas.0911863107
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule p21-activated kinase inhibitor PF-3758309 is a potent inhibitor of oncogenic signaling and tumor growth

Abstract: Despite abundant evidence that aberrant Rho-family GTPase activation contributes to most steps of cancer initiation and progression, there is a dearth of inhibitors of their effectors (e.g., p21-activated kinases). Through high-throughput screening and structure-based design, we identify PF-3758309, a potent (K d = 2.7 nM), ATP-competitive, pyrrolopyrazole inhibitor of PAK4. In cells, PF-3758309 inhibits phosphorylation of the PAK4 substrate GEF-H1 (IC 50 = 1.3 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
272
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(286 citation statements)
references
References 45 publications
9
272
0
1
Order By: Relevance
“…est concentration of the PAK inhibitor, which blocks PAK1/4 but not PAK2/3 (Murray et al, 2010); and (2) TEA-induced PAK phosphorylation was completely abolished only by the highest concentration of the PAK inhibitor, which suggests an additional contribution of PAK2/3 to the effect of TEA on PAK activation. Although previous work indicated that TBS-induced LTP consolidation did not require Rac/PAK signaling (Rex et al, 2009), we used a different PAK inhibitor (IPA-3), which does not interact with PAK4.…”
Section: Molecular Mechanisms For Activity-dependent Cytoskeletal Reomentioning
confidence: 97%
See 1 more Smart Citation
“…est concentration of the PAK inhibitor, which blocks PAK1/4 but not PAK2/3 (Murray et al, 2010); and (2) TEA-induced PAK phosphorylation was completely abolished only by the highest concentration of the PAK inhibitor, which suggests an additional contribution of PAK2/3 to the effect of TEA on PAK activation. Although previous work indicated that TBS-induced LTP consolidation did not require Rac/PAK signaling (Rex et al, 2009), we used a different PAK inhibitor (IPA-3), which does not interact with PAK4.…”
Section: Molecular Mechanisms For Activity-dependent Cytoskeletal Reomentioning
confidence: 97%
“…Two concentrations of PF-3758309 were used (50 and 500 nM), based on its different affinities for PAK1/4 versus PAK2/3 isoforms (Murray et al, 2010). Stimulation of PAK phosphorylation by TEA was significantly prevented by PF-3758309, but the effect was statistically significant only at the highest concentration (Fig.…”
Section: Bdnf-mediated Actin Polymerization In Hippocampal Slices Invmentioning
confidence: 99%
“…In addition, we employed another PAK inhibitor from Pfizer (PF-3758309), which potently suppresses both group I (PAK1, PAK2, and PAK3) and II (PAK4, PAK5, and PAK6) PAKs (44). Importantly, while both FRAX597 and PF-3758309 display some limited off-target effects on other kinases, these off-target effects are largely non-overlapping (45).…”
Section: Frax597 Inhibits Schwannoma Cell Proliferation In Vitro and mentioning
confidence: 99%
“…As such, therapeutic targeting of PAK1 in efforts to induce apoptosis of tumor cells has been advocated (3)(4)(5). PAK1 is one of six family members, categorized into two groups: PAK1-3 belong to group I and contain a unique autoinhibitory region, distinguishing them from Group II members PAK4 -6 (6).…”
mentioning
confidence: 99%